Pro-Angiogenesis Role of LINC00662 From Esophageal Squamous Cell Carcinoma Cells-Derived Extracellular Vehicles - Feng Li; Ren Niu; ShaoLin Gao; FangChao Zhao; Zefang Dong; Hao Zhang; Shujun Li (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: LINC00662 is oncogenic in some human cancers, but no much was revealed concerning to its specific action in tumor angiogenesis. Given that, our study investigated the role of LINC00662 from esophageal squamous cell carcinoma (ESCC) cells-derived extracellular vehicles (EVs) in angiogenesis through microRNA (miR)-195-5p/vascular endothelial growth factor A (VEGFA) axis.Methods: Clinical tissue samples were collected from patients with ESCC, in which LINC00662, miR-195-5p and VEGFA expression was analyzed. ESCC cells were transfected, from which EVs were isolated. Human umbilical vein endothelial cells (HUVECs) were co-cultured with the pretreated EVs. After that, viability, colony formation ability, invasion, migration and tube formation ability of HUVECs were observed. Tumor xenograft in nude mice was performed to detect the effect of LINC00662, miR-195-5p or EV specific inhibitor GW4869 on tumor development.Results: LINC00662 and VEGFA were upregulated while miR-195-5p was downregulated in the cancer tissue of patients with ESCC. EVs derived from ESCC cells promoted viability, colony formation ability, invasion and tube formation ability of HUVECs. Downregulation of LINC00662 or upregulation of miR-195-5p reversed the promotion of EVs derived from ESCC cells on the viability, colony formation ability, invasion and tube formation ability of HUVECs in vitro and in vivo. VEGFA overexpression reversed EVs carrying restored miR-195-5p induced effects on HUVECs in vitro.Conclusion: In summary, elevated LINC00662 transferred by ESCC cells-derived EVs induces angiogenesis through downregulating miR-195-5p and upregulating VEGFA.